Comparison of late adverse events after endoscopic sphincterotomy versus endoscopic papillary large balloon dilation for common bile duct stones: A propensity score‐based cohort analysis. Issue 4 (27th February 2018) - Maruta, Akinori; Iwashita, Takuji; Uemura, Shinya; Yoshida, Kensaku; Iwata, Keisuke; Mukai, Tsuyoshi; Doi, Shinpei; Yasuda, Ichiro; Imai, Kenji; Shimizu, Masahito
Abstract : Background and Aim: Endoscopic sphincterotomy (ES) is a standard procedure for the treatment of common bile duct stones (CBDS). Endoscopic papillary large balloon dilation (EPLBD) is emerging as an effective method to treat difficult CBDS, providing several advantages over ES without increasing early adverse events (AE). However, the late AE of EPLBD have not yet been well studied. The aim of the present study was to compare late AE after EPLBD versus ES for the treatment of CBDS using a propensity score‐based cohort analysis. Methods: Propensity score matching was introduced to reduce the possible bias in baseline characteristics between two treatment groups and formed the matched cohort including 240 patients. Primary endpoint was cumulative as well as estimated 1‐year and 3‐year late AE rates. Secondary outcome was the incidence of early AE. Results: Cumulative late AE rates were 12.5% and 16.7% in the ELPBD and ES groups ( P = 0.936) with a median follow‐up period of 915.5 and 1544.5 days, respectively. Estimated 1‐year and 3‐year late AE rates were 8.4% and 13.1% in the EPLBD group and 5.0% and 15.0% in the ES group, respectively. In multivariate analysis, ≥two procedures were identified as independent risk factors for late AE. Overall early AE rate did not differ between the groups. Conclusion: In the present study, late AE rate after EPLBD showed no significant difference compared with that after ES, which had a relatively long follow‐up period. Therefore, EPLBD could be used for the treatment of CBDS, if CBDS are considered difficult to treat. Clinical Trial Registry : UMIN000027798